Pengaruh Inflasi, Tingkat Suku Bunga, dan Kinerja Keuangan Terhadap Return Saham (Studi Empiris pada Perusahaan Consumer non-cyclicalss Yang Terdaftar di Bursa Efek Indonesia Periode 2017–2022) - Wijayanti, Siska; Aisyah Margie, Lyandra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine and empirically prove the influence of inflation, interest rates, and financial performance on stock returns (empirical study of non-cyclical consumer companies listed on the Indonesian Stock Exchange for the 2017 - 2022 period). The data used is secondary data, and the method used is panel data regression analysis with the help of e-views. The sample selected based on purposive sampling criteria was 21 companies. The results of this study show that inflation, interest rates, and financial performance simultaneously influence stock returns. Partially, inflation and financial performance influence stock returns. However, interest rates do not affect stock returns.